Biobased flexible aromatic polyester poly(1, 5-pentylene terephthalate) (PPeT): Revisiting melt crystallization behaviors and thermo-mechanical properties. (January 2019) - Lu, Jing; Zhou, Lizhong; Xie, Hongzhou; Wu, Linbo; Li, Bo-Geng
Graphical abstract: Synopsis. High molecular weight biobased poly(1, 5-pentylene terephthalate) was synthesized and found to be flexible polyester with slow melt crystallizability and very ductile tensile properties. Highlights: High MW PPeT was synthesized from biobased 1, 5-pentanediol an terephthalic acid. Nonisothermal melt crystallization of PPeT is observed for the first time. PPeT crystallizes from melt slowly but rapidly from glass state. As a thermoplastic, PPeT shows ductility & tensile properties comparable to HDPE. PPeT exhibits excellent thermal stability. Abstract: Poly(1, 5-pentylene terephthalate) (PPeT) is a less studied member of the family of terephthalic polyesters. The presence of flexible pentylene moiety and foreseeable commercialization of bio-based 1, 5-pentanediol (PeDO) could make PPeT an attractive polymer. However, as a semi-crystalline flexible polyester, previous studies indicated that PPeT was hardly to crystallize nonisothermally from melt and showed clear brittleness. In this study, high molecular weight biobased PPeT (0.75 dL/g) was synthesized via melt polycondensation of terephthalic acid and biobased PeDO. It was characterized with 1 H NMR and FTIR, and its crystallization/melting behaviors and thermo-mechanical properties were assessed with DSC, WAXD, TGA and tensile test. Different from previous reports, it is found that this high molecular weight PPeT product can crystallize slowly from melt, showing half crystallization time of 3.4 min when isothermally crystallized at 70 °C and melt crystallization enthalpy of 5.0 J/g at 61 °C when nonisothermally crystallized at cooling rate of 10 °C/min. It behaves as a typical flexible thermoplastic with excellent ductility rather than a brittle polymer, showing tensile modulus of 650 MPa, tensile stress at break of 21 MPa and elongation at break of 450%. It also exhibits excellent thermal stability.